Olhar sensível - pensante de crianças: visualidades na/da escola nos anos iniciais do Ensino Fundamental - Souza, Ana Cristina Luiza (2021)
This thesis is based on the assumption that the school is a producer of visual culture and that the visualities it produces go beyond the decorative, didactic and expository functions, because they exercise a visual pedagogy, which indicate ways of seeing childhoods and how to be a child. Our main goal is to understand what are the visualities of/in the daily life of a school in the early years of elementary school. In this sense, some questions guide this research: Which images make up the visual school collection in a public school of the early years of elementary school? Where do these images come from? Who produces them? What do they say or present about childhood? What do children say about these school images/visualities? What is the importance of school visualities in the education of children's looks and in the practice of teaching and understanding childhoods? Therefore, the specific objectives of this research are: (1) To investigate the visual collections of the different ambiences of a public school of the early years of elementary education; (2) To reflect on the looks of children on the school visualities; (3) To reflect on the importance of the visualities of/in the school, their articulations with the education of the children's looks and the practice of teaching and understanding childhoods. The present research was developed in a qualitative methodological and epistemological approach guided especially by González Rey (2005), of the ethnographic type, as addressed by André (1995). Five teachers and 23 children from the 4th year of elementary school (between 9 and 10 years old) from a public school in Buriti Alegre, Goiás, took part in the research. The information constructed in the research was analyzed in the theoretical contribution of Visual Culture studies and in the dialog of studies about children and childhood from Sociology, Anthropology and Education. The instruments for the construction of the information were: preparation of a photographic inventory of the school's visuals; observations with field diary notes; conversations with children and teachers; image reading and drawing. The research results show that the visualities produced at school reveal conservative visions and versions of childhood, marked by the passivity of children and by the hierarchy of the adult over them, reinforcing hegemonic standards, values and norms for children. The children, in turn, when provoked to think about the school visualities, demonstrate critical and sensitive capacity in face of the images of these visualities. We conclude that the visualities produced at school do little to favor an education of the children's look in order to broaden their views about themselves and about the world.